'They were a little family': an exploratory study of parental involvement in nurture groups – from a practitioner and parent perspective. (March 2014) - Kirkbride, Rebecca
<x xml:space="preserve">Abstract</x> The approach taken by nurture groups emphasises that difficult early experiences can be modified through creating opportunities to develop security and attachment from alternative sources other than parents. Despite previous research indicating the positive impact parental involvement can have on both parents and children, research into parental involvement in nurture groups has been identified as being sparse and requiring further investigation. This exploratory study provides an insight into the perceptions of parents and nurture group staff regarding parental involvement. In‐depth qualitative data were collected from semi‐structured interviews with parents and nurture group staff. Inductive thematic analysis was applied to draw out themes from the data. Findings highlight different experiences of parents and staff, but also common themes of relationships, communication and sharing practice. Findings are discussed in relation to the research questions and the relevant literature regarding parental involvement. Implications for nurture groups and schools are discussed.